2013
DOI: 10.1177/0142723713479435
|View full text |Cite
|
Sign up to set email alerts
|

Lexical retrieval for nouns and verbs in typically developing bilectal children

Abstract: Previous evidence shows that nouns are easier for many language users to retrieve than verbs, but scant research has been conducted with children in bilectal environments (where both standard and non-standard forms of a language are spoken). This study investigates object and action naming in children who are native speakers of a nonstandard variety, Cypriot Greek (CG), but instructed scholastically in the official variety, Standard Modern Greek (SMG). Participants were typically developing Greek Cypriot presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…There is a wealth of research spanning half a century on grammatical class effects exemplified by the noun–verb dissociation in language production. Evidence over the years for a noun superiority over verbs, or possibly vice versa, in spoken naming has come from a wide variety of sources such as the following, non-exhaustive list: aphasia resulting from stroke classified as either Broca's aphasia (agrammatism) or anomic aphasia (e.g., Jonkers and Bastiaanse, 1998 ; Luzzatti et al, 2002 ; Kambanaros, 2008 ; Franco et al, 2012 ; Franco, 2014 ); left subcortical lesions and concomitant anomia (Kambanaros and van Steenbrugge, 2006 ); non-focal or diffuse brain pathology such as dementia (Miozzo et al, 1994 ; Robinson et al, 1996 ; White-Devine et al, 1996 ; Bushell and Martin, 1997 ; Silveri and di Betta, 1997 ; Cappa et al, 1998 ), Alzheimer's disease (Druks et al, 2006 ), and primary progressive aphasia (Thompson et al, 2012 ); motor-related neurological diseased groups such as Parkinson's disease (see Herrera and Cuetos, 2012 for an update), progressive supranuclear palsy (Daniele et al, 2013 ), and corticobasal degeneration (Silveri and Ciccarelli, 2007 ); psychiatric disorders, including schizophrenia (Kambanaros et al, 2010 ); developmental language disorders, most prominently specific language impairment, henceforth SLI (Sheng and McGregor, 2010 ; Kambanaros et al, 2013a , b ); genetic syndromes such as Williams syndrome (Thomas et al, 2006 ); bi- and multilingual individuals who show the noun–verb dissociation in all their spoken languages, such as multilingual patients with aphasia following stroke (Kambanaros and van Steenbrugge, 2006 ; Kambanaros, 2009b ; Faroqi-Shah and Waked, 2010 ), primary progressive aphasia (Hernández et al, 2008 ), multiple sclerosis (Calabria et al, 2014 ), and multilingual children with SLI (Kambanaros et al, 2013a , 2014 ); modality-specific dissociations, that is, disproportionate impairments in naming words from one grammatical class (nouns or verbs) in the spoken or written modality only (Caramazza and Hillis, 1991 ; Hillis and Caramazza, 1995 ; Rapp and Caramazza, …”
Section: Aims and Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a wealth of research spanning half a century on grammatical class effects exemplified by the noun–verb dissociation in language production. Evidence over the years for a noun superiority over verbs, or possibly vice versa, in spoken naming has come from a wide variety of sources such as the following, non-exhaustive list: aphasia resulting from stroke classified as either Broca's aphasia (agrammatism) or anomic aphasia (e.g., Jonkers and Bastiaanse, 1998 ; Luzzatti et al, 2002 ; Kambanaros, 2008 ; Franco et al, 2012 ; Franco, 2014 ); left subcortical lesions and concomitant anomia (Kambanaros and van Steenbrugge, 2006 ); non-focal or diffuse brain pathology such as dementia (Miozzo et al, 1994 ; Robinson et al, 1996 ; White-Devine et al, 1996 ; Bushell and Martin, 1997 ; Silveri and di Betta, 1997 ; Cappa et al, 1998 ), Alzheimer's disease (Druks et al, 2006 ), and primary progressive aphasia (Thompson et al, 2012 ); motor-related neurological diseased groups such as Parkinson's disease (see Herrera and Cuetos, 2012 for an update), progressive supranuclear palsy (Daniele et al, 2013 ), and corticobasal degeneration (Silveri and Ciccarelli, 2007 ); psychiatric disorders, including schizophrenia (Kambanaros et al, 2010 ); developmental language disorders, most prominently specific language impairment, henceforth SLI (Sheng and McGregor, 2010 ; Kambanaros et al, 2013a , b ); genetic syndromes such as Williams syndrome (Thomas et al, 2006 ); bi- and multilingual individuals who show the noun–verb dissociation in all their spoken languages, such as multilingual patients with aphasia following stroke (Kambanaros and van Steenbrugge, 2006 ; Kambanaros, 2009b ; Faroqi-Shah and Waked, 2010 ), primary progressive aphasia (Hernández et al, 2008 ), multiple sclerosis (Calabria et al, 2014 ), and multilingual children with SLI (Kambanaros et al, 2013a , 2014 ); modality-specific dissociations, that is, disproportionate impairments in naming words from one grammatical class (nouns or verbs) in the spoken or written modality only (Caramazza and Hillis, 1991 ; Hillis and Caramazza, 1995 ; Rapp and Caramazza, …”
Section: Aims and Backgroundmentioning
confidence: 99%
“…developmental language disorders, most prominently specific language impairment, henceforth SLI (Sheng and McGregor, 2010 ; Kambanaros et al, 2013a , b );…”
Section: Aims and Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, some researchers have concluded that the grammatical class effect may derive from access to, and the connections between, the lemma and lexeme levels, rather than the representation at either level per se (e.g., Hanley et al, 2013;Howard & Gatehouse, 2006;Kambanaros & Grohmann, 2015;Kambanaros et al, 2013;Kambanaros et al, 2014). Though most of these studies have used Levelt's (1989;Levelt et al, 1999) model as their theoretical framework, connectionist computational modeling has also shown that the links between meaning and form can be impacted separately from either representation (Li & Farkaš, 2002;Li, Farkaš & MacWhinney, 2004).…”
Section: Discussionmentioning
confidence: 99%